Viability of transarctic shipping routes: a literature review from the navigational and commercial perspectives. Issue 1 (2nd January 2017) - Meng, Qiang; Zhang, Yiru; Xu, Min
ABSTRACT: The continuous ice retreat in the Arctic has fueled speculations of new transarctic shipping routes to be operational soon. While the media vigorously propagates the great potentials of these routes, researchers have accessed the feasibility of opening of transarctic shipping routes from various perspectives; diverse and some polarized conclusions have emerged. This paper aims to critically review the studies that examine the necessary conditions and requirements that make transarctic shipping routes sufficiently viable. We mainly focus on two aspects: navigation conditions and commercial features. Selected studies are analyzed and compared in depth. Finally, possible future research directions are put forward.This article is a revised and expanded version of a paper entitled Viability of Transarctic Shipping Routes: An Overview, presented at the International Conference on 'Global Integration of Economies and Connectivity Development' in Taiwan on 31 August 2015.